Effect of ethanedioic acid functionalization on Ni/Al2O3 catalytic hydrodeoxygenation and isomerization of octadec-9-enoic acid into biofuel: Kinetics and Arrhenius parameters - Ayodele, O.B.; Lethesh, K.C.; Gholami, Z.; Uemura, Y. (Elsevier, 2016)
The effect of ethanedioic acid (EdA) functionalization on Al2O3 supported Ni catalyst was studied on the hydrodeoxygenation (HDO), isomerization, kinetics and Arrhenius parameters of octadec-9-enoic acid (OA) into biofuel in this report. This was achieved via synthesis of two catalysts; the first, nickel alumina catalyst (Ni/Al2O3) was via the incorporation of inorganic Ni precursor into Al2O3; the second was via the incorporation nickel oxalate (NiOx) prepared by functionalization of Ni with EdA into Al2O3 to obtain organometallic NiOx/Al2O3 catalyst. Their characterization results showed that Ni species present in Ni/Al2O3 and NiOx/Al2O3 were 8.2% and 9.3%, respectively according to the energy dispersive X-ray result. NiOx/Al2O3 has comparably higher Ni content due to the EdA functionalization which also increases its acidity and guarantees high Ni dispersion with weaker metal-support-interaction leading to highly reducible Ni as seen in the X-ray diffraction, X-ray photoelectron spectroscopy, TPR and Raman spectroscopy results. Their activities tested on the HDO of OA showed that NiOx/Al2O3 did not only display the best catalytic and reusability abilities, but it also possesses isomerization ability due to its increased acidity. The NiOx/Al2O3 also has the highest rate constants evaluated using pseudo-first-order kinetics, but the least activation energy of 176 kJ/mol in the biofuel formation step compared to 244 kJ/mol evaluated when using Ni/Al2O3. The result is promising for future feasibility studies toward commercialization of catalytic HDO of OA into useful biofuel using organometallic catalysts.